Effective Aid for Hitting the Bull's Eye; Comment on "It's About the Idea Hitting the Bull's Eye": How Aid Effectiveness Can Catalyse the Scale-up of Health Innovations" - Elvira Beracochea (Kerman University of Medical Sciences, 2018)
This article studies how six key aid effectiveness principles for "Hitting the bull's eye" can bring about the scale up of maternal and newborn health (MNH) interventions. These key principles are based on accepted international agreements such as the Paris Declaration on Aid Effectiveness. The results indicate that the six principles should be a guide for recipient countries to take ownership of the development process and work with donors to plan effective coordination structures. Countries that take ownership will be able to work with donors and implementers to not only test new interventions that address pressing challenges to deliver quality MNH care but also include the successful knowledge transfer and handover of these interventions, the effective integration of the new intervention as part of the country's health system and a costed scale-up plan. The article could have been strengthened with clear and actionable recommendations for the three countries to improve their ownership of donor-funded assistance, but it showed that there is need to change how aid is delivered and that embracing and applying these principles will help countries take ownership of MNH programs and lead the dialog and effective scale up with those involved. The authors should be commended on taking the lead in the field of aid effectiveness, and encouraged to conduct quantitative and further qualitative measurements of the application of their findings in the three counties included in the study.